2023
DOI: 10.1590/1517-8692202329012022_0543
|View full text |Cite
|
Sign up to set email alerts
|

Balance Training and Physical Ability of Basketball Players

Abstract: Introduction Balance in gait is a fundamental factor for rhythmic changes on the court, and physical fitness is a basic requirement for competitiveness in basketball. Objective Analyze the effects of balance training on the gait and physical fitness of basketball players. Methods Thirty basketball athletes were selected and randomly divided into a control and experimental group. A balance training program including balls was added to the experimental group, while the control group followed only the tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The training techniques employed in these studies involve only a portion of the fitness training approach, including endurance training, balance training, and strength training. Some studies support the findings of earlier research that showed that fitness training can enhance athletes' abilities [56][57][58]. In fact, the same rationale that supports the positive effects of fitness training on athletes' specialized skills in other sports likely applies to the short-passing abilities of soccer players.…”
Section: Fitness Trainingsupporting
confidence: 74%
“…The training techniques employed in these studies involve only a portion of the fitness training approach, including endurance training, balance training, and strength training. Some studies support the findings of earlier research that showed that fitness training can enhance athletes' abilities [56][57][58]. In fact, the same rationale that supports the positive effects of fitness training on athletes' specialized skills in other sports likely applies to the short-passing abilities of soccer players.…”
Section: Fitness Trainingsupporting
confidence: 74%
“…Conversely, balance training, another pivotal rehabilitative strategy, focuses on enhancing proprioception and postural control. This form of training incorporates both static and dynamic exercises, often utilizing specialized equipment such as balance boards, wobble boards, or foam pads (10)(11)(12). These tools aid in creating an unstable environment, forcing the ankle and surrounding muscles to engage in order to maintain balance.…”
Section: Introductionmentioning
confidence: 99%